TYPES AND FORMS OF PROFESSIONAL DEVELOPMENT OF A PRESCHOOL TEACHER IN IN-SERVICE TRAINING - Machynska, Nataliia; Derkach, Yuliya; Pankevych, Yuliya (Continuing Professional Education: Theory and Practice, 2020)
The article is devoted to the practical aspects of forming the professional readiness of preschool teachers for life-long professional development. It is shown that the professional development of practicing teacher can be embodied in certain forms, in particular: specialized on-the-job training; coaching and / or advisory interactions with the professional oriented communities sharing the experience or peer training groups. In the article it is stated that pedagogical trainings are the effective form of methodological work in the preschool education establishment, the main purpose of which is the formation of readiness of teachers for professional development during life. The advantages and difficulties in conducting trainings are outlined. It is pointed out that the success of the training depends crucially on the so-called «group effect». The authors provide a description of the content characteristics and practical importance of various forms of methodological work in pre-school educational establishment, in particular: trainings, certified courses (innovative form of professional growth of teachers), business games (form and method of active teacher training), exercises (a method of teaching that involves purposeful learning), repeated repetition of certain actions or operations for the purpose of formation of skills), methodical associations (structural unit of the methodical service of the educational establishment providing the educational training, methodical research and experimental work), training (acquisition by a person experiences the tasks and responsibilities of a specialty) and others. Examples of trainings, business games and exercises, directions for methodological associations, workshops, and internship topics are provided with a clear description of their goals and objectives. It is shown that the professional growth of a preschool teacher depends on a set of different factors, including the level of motivational readiness generated and the selection of interactive forms and methods of methodical work that are appropriate to use in working with preschool teachers.